EBP2, a Human Protein That Interacts with Sequences of the Epstein-Barr Virus Nuclear Antigen 1 Important for Plasmid Maintenance - Shire, Kathy (American Society for Microbiology, 1999)
The replication and stable maintenance of latent Epstein-Barr virus (EBV) DNA episomes in human cells requires only one viral protein, Epstein-Barr nuclear antigen 1 (EBNA1). To gain insight into the mechanisms by which EBNA1 functions, we used a yeast two-hybrid screen to detect human proteins that interact with EBNA1. We describe here the isolation of a protein, EBP2 (EBNA1 binding protein 2), that specifically interacts with EBNA1. EBP2 was also shown to bind to DNA-bound EBNA1 in a one-hybrid system, and the EBP2-EBNA1 interaction was confirmed by coimmunoprecipitation from insect cells expressing these two proteins. EBP2 is a 35-kDa protein that is conserved in a variety of organisms and is predicted to form coiled-coil interactions. We have mapped the region of EBNA1 that binds EBP2 and generated internal deletion mutants of EBNA1 that are deficient in EBP2 interactions. Functional analyses of these EBNA1 mutants show that the ability to bind EBP2 correlates with the ability of EBNA1 to support the long-term maintenance in human cells of a plasmid containing the EBV origin, oriP. An EBNA1 mutant lacking amino acids 325 to 376 was defective for EBP2 binding and long-term oriP plasmid maintenance but supported the transient replication of oriP plasmids at wild-type levels. Thus, our results suggest that the EBNA1-EBP2 interaction is important for the stable segregation of EBV episomes during cell division but not for the replication of the episomes.